Movement, resource selection, and the physiological stress response of white-bearded wildebeest - Stabach, Jared A., author; Boone, Randall B., advisor; Florant, Gregory, committee member; Reid, Robin S., committee member; Wittemyer, George, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Keywords: glucocorticoids; Kenya; wildebeest; habitat fragmentation; animal movement; resource selection